The Impacts of Nano Barium Titanate on The Radiopacity and Surface Roughness of 3D-Printed Acrylic Denture Base - Rand Naseer Kadhum; Thekra Ismael Hamad ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
The creation of three dimensional (3D)-printed denture base was made possible by the advent of additive manufacturing technology. This research intends to test the effect of inclusion barium titanate nanoparticles (BaTiO3NPs) at different weight percentages on the radiopacity and surface roughness of 3D-printable denture bases. Three groups were created: a control group, 0.5 wt.%, and 1 wt.% BaTiO3NPs. Every sample was tested for surface roughness utilizing contact profilometer and atomic force microscope (AFM), and the radiopacity by measuring optical density using transmission densitometer. Adding BaTiO3NPs to 3D-printable resin improved the radiopacity and decreased the surface roughness of the modified groups.DOI: https://doi.org/10.54633/2333-024-056-007